2008
DOI: 10.1080/00207540701452142
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management practices as a mediator of the relationship between operations capability and firm performance

Abstract: The current study uses mediated regression analysis and structural equation modelling to test the proposition that supply chain management practices mediate the relationship between operations capability and firm performance. Operations capability is defined in terms of a firm's new product design and development, total quality management and just-in-time capabilities. Results support the research model and also suggest the existence of a direct relationship between operations capability and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 76 publications
8
125
0
17
Order By: Relevance
“…Therefore, achieving the superior performance on hotel's operation capability can lead to the superior financial performance for a long period. This result is consistent with the operational extant literature (Hsu et al, 2009;Tan et al, 2007). However, operations capability is highly significant for both efficient and inefficient hotels, indicating the absence of any moderating effect of efficiency on the relationship between operations capability and performance.…”
Section: 1operations Capabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, achieving the superior performance on hotel's operation capability can lead to the superior financial performance for a long period. This result is consistent with the operational extant literature (Hsu et al, 2009;Tan et al, 2007). However, operations capability is highly significant for both efficient and inefficient hotels, indicating the absence of any moderating effect of efficiency on the relationship between operations capability and performance.…”
Section: 1operations Capabilitysupporting
confidence: 82%
“…Similarly, though several studies discussed earlier highlighted positive relationships between environmental capabilities and firm performance, other such as Hitchens et al (2005) and Margolis and Walsh (2003) have not found such significant relationships, while Vogel (2005) argued for more complex relationships. Similar arguments can also be found on the relationship between operations capabilities and performance (e.g., Hsu et al, 2009). In spite of these studies arguing for non-existence or existence of complex relationships, our study highlights that there is evidence for direct and positive relationships between the three capabilities and financial performance.…”
Section: Conclusion Limitation and Directions For Future Researchmentioning
confidence: 54%
“…Huge investments in IT systems have enabled companies to share considerable volumes of data and information along the supply chain, making real-time collaboration possible among the partners of the supply chain, as well as enhancing inventory management and distribution. As some researchers believe, ERP enables data and information processing and transmission which is essential for synchronous decision-making and SCM competencies (Hsu, Tan, Kannan, & Keong Leong, 2009;Sanders, 2007). Moreover, myriad number of ERP equipped companies have extended the scope of the system to incorporate their customers and suppliers into the system to provide more e-business or e-commerce services and to enhance the functionalities of the supply chain (Olhager & Selldin, 2003).…”
Section: Enterprise Resource Planning and Supply Chain Managementmentioning
confidence: 99%
“…Así, algunos autores han buscado desde la perspectiva de la competitividad de las empresas basada en una estrategia productiva avanzada y soportada en prácticas y técnicas de dirección de la producción y operaciones, identificar cómo su uso afecta a los resultados empresariales (Hsu et al, 2009, Daniel, 2006, Sousa, 2003, Sakakibara et al, 1997, Flynn et al, 1995a. Otros han buscado hacerlo desde la perspectiva de la calidad (Denis and Rodney, 2004, Denis and Rodney, 2003, Denis and Rodney, 2002, Joanna Hing Yee and Jiju, 2001, Sohal and Terziovski, 2000, Dow et al, 1999, Flynn et al, 1995b; siendo las aproximaciones relativas al ámbito de las técnicas y herramientas relativas a la gestión de la I+D, el lanzamiento y desarrollo de nuevos productos, y la gestión de proyectos los más cercanos al ámbito de la innovación empresarial.…”
Section: Antecedentes a Las Técnicas Y Herramientas De Gestión De La unclassified